La città come misura. Progetti per la Pignasecca - Addario, Francesca; Cutillo, Raffaele; Visconti, Federica (TeA / Teaching Architecture, 2022)
The book collects the outcomes of the three Architectural Design Studios of the second year of the Bachelor degree course in Science of Architecture of the DiARC_ Department of Architecture of the University of Naples "Federico II" held during the academic year 2020/21. The three ateliers, sharing the same theme and place, worked on Naples and, in particular, within one of those parts - the Pignasecca - that make up its compact body, confronting the existing and taking it as a reference and measure for the contemporary project. On the basis of these premises, the publication is not limited to an orderly account of a teaching experience, but aims to be a testimony of convinced adhesion to the initiative of coordination of all the Studios of SSD ICAR/14-Architectural and Urban Composition at DiARC: to respond to the need to expand opportunities for comparison and dialogue and to reaffirm the centrality of the project in architectural studies